Atomistic understanding of the C·T mismatched DNA base pair tautomerization via the DPT QM and QTAIM computational approaches - Brovarets', Ol'ha O (Journal of computational chemistry, 2013)
Copyright © 2013 Wiley Periodicals, Inc.